Direct and rapid effects of 3, 5-diiodo-L-thyronine (T2). (15th December 2017) - Moreno, Maria; Giacco, Antonia; Di Munno, Celia; Goglia, Fernando
Abstract: A growing number of researchers are focusing their attention on the possibility that thyroid hormone metabolites, particularly 3, 5-diiodothyronine (T2), may actively regulate energy metabolism at the cellular, rather than the nuclear, level. Due to their biochemical features, mitochondria have been the focus of research on the thermogenic effects of thyroid hormones. Indeed, mitochondrial activities have been shown to be regulated both directly and indirectly by T2-specific pathways. Herein, we describe the effects of T2 on energy metabolism. Highlights: An overview of direct and rapid effects of 3, 5-diiodothyronine is proposed. The mechanism relies on regulation of mitochondrial activities. 3, 5-Diiodothyronine plays a role in thyroid endocrinology.